Three-dimensional reconstruction of the spinal cord of thoroughbred - Durmuş Bolat (Eurasian Journal of Veterinary Sciences)
The aim of this study was to three-dimensional reconstruction of cervical part of the spinal cord of a thoroughbred horse using its histological sections with the help of 3d reconstruction module of stereo investigator. Scanned images using Office flatbed scanner were opened as image stacks in stereo investigator. Considering real measurements of the segments, borders of the gray and white matter and central canal were drawn by planimetric methods. This procedure was performed on all consecutive sections. All drawn lines of segments were matched to each other using mentioned software. Finally, three-dimensional reconstruction of segments was obtained using 3D reconstruction module. Surface area, cross-sectional area and volume of the segments were calculated by Neurolucida explorer software. Obtained results from 3D models were given in tabular form. It is thought that obtained three-dimensional models possessed real measurements of the segments contribute to anatomy of region of interest, can be used as digital education materials and obtaining solid materials exporting three-dimensional models to 3D printers improve the quality of education and training in anatomy.